2016
DOI: 10.2174/1872208310666160922111704
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Concentration in Periwinkle - Tympanotomus fuscatus in Iko River Estuary, Nigeria

Abstract: Except for Mercury, the mean concentration of the metals was above the maximum permissible limits recommended by relevant bodies and organizations. Hence, there is need for regular monitoring of heavy metal concentrations in this water body and the aquatic organism inhabitants because of the long term effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…32 Lead values ranging from 0.02 to 0.21 mg/kg were recorded for periwinkles obtained from Uta-Ewa creek, Imo River Estuary, Nigeria. 33 In a study of heavy metals in seafoods and farm produce in Uyo, Nigeria, a higher mean value (0.34 mg/kg) was recorded for Pb in periwinkle. 1 A higher mean value of 55.88±14.28 was also reported for periwinkle obtained from the Benin River, Nigeria.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…32 Lead values ranging from 0.02 to 0.21 mg/kg were recorded for periwinkles obtained from Uta-Ewa creek, Imo River Estuary, Nigeria. 33 In a study of heavy metals in seafoods and farm produce in Uyo, Nigeria, a higher mean value (0.34 mg/kg) was recorded for Pb in periwinkle. 1 A higher mean value of 55.88±14.28 was also reported for periwinkle obtained from the Benin River, Nigeria.…”
Section: Discussionmentioning
confidence: 98%
“…39 The range of Cd concentrations recorded in this study was lower than the range of 0.59–0.93 mg/kg reported for periwinkles obtained from Uta-Ewa creek, Imo River Estuary, Nigeria. 33 A mean value of 0.02 mg/kg was reported for the upper reaches of the Bonny Estuary, Nigeria. 31 Lower values (0.001–0.003 mg/kg) were reported for periwinkle harvested from perturbed tropical mangrove forests in the Niger Delta, Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…For instance shellfishes (U. tangeri, C. amnicola, T. fuscatus, P. monodon), along the Opuro-Ama Creek in Rivers State (Chris and Oghenetekevwe 2022), Senilia senilis (Blood Cockle) and Crassostrea gasar (Oyster) from Bonny Estuary, Rivers State (Dike et al 2022), Sarotherodon melanotheron (Blackchin tilapia) from Woji creek, Rivers State (Ihunwo et al 2022), three different species of catfishes Chrysichthys nigrodigitatus (marine catfish),Clarias gariepinus (african catfish), and Schilbe mystus (silver catfish) in Ikoli Creek, Yenagoa, Bayelsa State (Ighariemu, Belonwu, and Wegwu 2019c), three selected fin fish species; Oreochromis niloticus, Synodontis clarias, and Hepsetus odoe from Oguta lake (Ogueri, Adebayo, and Nwaiwu 2018), fish samples from six Rivers in Delta state viz: Egbokodo River in Warri, River Ethiope in Sapele, Urie River in Igbide Isoko, Asaba-Ase creek, Aragba River in Abraka, and Uzere Creek (Ubiogoro and Adeyemo 2017). Genyonamus lineatus (Croaker fish) from Bonny and Finima, Rivers State (Abarshi, Dantala, and Mada 2017), Callinectis amnicola (swimming crabs) from Azuabie estuarine creek, Rivers State (Moslen and Miebaka 2017), Tympanotomus fuscatus (Periwinkle) from Iko river estuary, Akwa Ibom State (Abiaobo, Udi, and Obot 2016), seafoods from Ethiope river, Warri Delta State (Uhegbu et al 2012), Seafoods (T. guineensis, L. falcipinis, C. pallidus, and P. notialis) from Ogoniland, Rivers State (Nkpaa et al 2016). This study showed higher values of heavy metal concentrations than all compared scholarly research cited within the Niger region with an exception of (Ubiogoro and Adeyemo 2017) study on multiple rivers and creek that has high level of Iron (Fe) bioconcentrated in different fishes and (Ihunwo et al 2022) study on Woji Creek that has high level of Pb in Sarotherodon melanotheron due to waste deposition and other anthropogenic activities on the intertidal creek.…”
Section: Comparison Of Metal Concentrationmentioning
confidence: 99%